Comparison of the growing habit of peach varieties trained to caldron and slender spindle crowns - Szőke, S.; Csihon, Á. (International Journal of Horticultural Science, 2010)
Six peach varieties (’RedMoon’, ’Early Redhaven’, ’Rich Lady’, ’Suncrest’, ’Silver King’, ’Royal Glory’) grafted on seedling stock have been trained alternatively, to caldron (kettle) and to slender spindle, are compared in dormant stage regarding their variety-specific growing habits. According to our results, marked differences have been stated in vegetative vigour of varieties measured as the length, thickness and number of shoots. The caldron crowns displayed more vigour whereas the spindle trees produced more balanced and moderately growing shoots. The differences due to varieties were more conspicuous that due to the training. An intrinsic knowledge of growing habits of varieties may facilitate the development of variety-specific pruning technologies beginning with the training for crown forms.